Interoperable Learning Systems Using Open Educational Standards (Journal of Digital Learning Futures p-ISSN 3117-6054 and e-ISSN 3117-6062, 2025)
Educational technology ecosystems are fragmented across dozens of incompatible LMS platforms, content repositories, assessment tools, and learner record systems. Open educational standards -- IMS Global specifications including LTI (Learning Tools Interoperability), xAPI (Experience API), QTI (Question and Test Interoperability), CASE (Curriculum Architecture Standards Exchange), and the emerging Comprehensive Learner Record (CLR) -- provide protocol-level specifications for interoperability that enable learning systems to exchange content, activity data, and learner credentials across institutional and vendor boundaries. Despite widespread adoption of individual standards, implementing complete cross-standard interoperability -- where a learner's xAPI activity stream from one platform feeds adaptive recommendations in another -- remains architecturally complex. This paper proposes the Open Educational Standards Interoperability Framework (OESIF), a systematic evaluation of five standards (LTI 1.3, xAPI 2.0, QTI 3.0, CASE 1.0, CLR 2.0) and their integration patterns across 14 real LMS deployments in six countries. OESIF introduces the Standards Integration Score (SIS) and identifies five architectural interoperability patterns. Key results: LTI 1.3 achieves the highest adoption (SIS = 0.924, deployed in 13/14 LMS systems); xAPI 2.0 achieves highest cross-platform data portability (SIS = 0.884); CLR 2.0 emerges as the critical missing link for lifelong learning credential portability. The framework provides an interoperability implementation roadmap for educational technology architects.